Oscillatory exchange bias effect in La0.67Sr0.33MnO3/G-SrMnO3/La0.67Sr0.33MnO3 sandwiches. (26th June 2015) - Mao, H J; Li, F; Xiao, L R; Wang, Y Y; Cui, B; Peng, J J; Pan, F; Song, C
Abstract: We investigate the exchange bias effect in La0.67 Sr0.33 MnO3 / G -SrMnO3 / La0.67 Sr0.33 MnO3 (LSMO/SMO/LSMO) sandwiches, where the spacer is a G -type antiferromagnet. Because of the cycloid bulk spins in the SMO modulated by the top LSMO layer, the sandwich structure exhibits an oscillatory exchange bias behavior as a function of the SMO thickness. This unprecedented phenomenon vanishes in LSMO/SMO bilayers, where the exchange bias saturates as the SMO thickness increases, giving rise to the antiferromagnetic anisotropy constant of SMO, 1.0 –2.0   ×   10 5  erg cm −3 . The results provide a broad opportunity to tailor antiferromagnetic moments by interfacial design for antiferromagnet spintronics.